The Ottoman and 20th-Century Village of Jafrakani Kon: A Rescue Excavation in the Soran District (Iraqi Kurdistan) - Helms, Tobias; Kerig, Tim (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
In this article, we discuss results of a building survey and a rescue excavation at the site of Jafrakani Kon (district of Soran, Khalifan sub-district, Iraqi Kurdistan). Archaeological field work at Jafrakani Kon aimed to record terraced grounds and other stone-built structures and to retrieve dating evidence from two test trenches. Most features and finds recorded on-site can be dated to the Late Ottoman/early post-Ottoman period. We also report the natural and oral history as far as it can be of use for interpreting the archaeological finds. The paper gives a summary of our findings (especially the Ottoman/post-Ottoman rural hand-made pottery) and provides an anchor point for future research in the region. We stress the importance of the archaeology of the more recent periods of Iraqi Kurdistan.